1986
DOI: 10.1016/s0006-3495(86)83722-5
|View full text |Cite
|
Sign up to set email alerts
|

Water molecule dynamics in hydrated lysozyme. A deuteron magnetic resonance study

Abstract: Proton nuclear magnetic resonance relaxation investigations of water dynamics in hydrated protein powders have the serious drawback that protein-water intermolecular dipolar interactions make the unambiguous interpretation of the results difficult. To circumvent this difficulty, deuteron spin-lattice and spin-spin relaxation times in lysozyme powder hydrated with deuterium oxide were measured as a function of temperature and at two frequencies. Although the deuteron relaxation results are compatible with a wat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
10
0

Year Published

1987
1987
2007
2007

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 19 publications
4
10
0
Order By: Relevance
“…The correlation time for the fast reorientation of the water molecules about the hydrogen bond axis is 5 x 10-10 < Tr < 8 x 10-9 s. While Tr is about three orders of magnitude slower than the correlation time for bulk water motion, the correlation time for the tumbling of the water molecules (1.5 x 10-7 < Tt < 8 x 10 -7 S) iS about five orders of magnitude slower than that of bulk water. These values agree with previous estimates from hydrated macromolecular systems (22,43,46).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The correlation time for the fast reorientation of the water molecules about the hydrogen bond axis is 5 x 10-10 < Tr < 8 x 10-9 s. While Tr is about three orders of magnitude slower than the correlation time for bulk water motion, the correlation time for the tumbling of the water molecules (1.5 x 10-7 < Tt < 8 x 10 -7 S) iS about five orders of magnitude slower than that of bulk water. These values agree with previous estimates from hydrated macromolecular systems (22,43,46).…”
Section: Discussionsupporting
confidence: 92%
“…The values of the tumbling and fast reorientation correlation times reported in this work have been confirmed by T1, dispersion measurements on low hydration NaDNa in which it has been found that the Tl, of the water protons is nondispersive (35). These values for the correlation times also agree with those determined in studies on hydrated biopolymers with similar water contents (22,43,46).…”
Section: Implications Of Neglecting Cross-relaxationsupporting
confidence: 86%
“…It has been shown (Peemoeller et al 1986;Schreiner et al 1991) that the water molecule residence time at hydration sites in polymer powders is expected to be less than a microsecond. It is not unreasonable to expect a similar result for water in wood.…”
Section: Discussionmentioning
confidence: 99%
“…In the following NMR studies [46,47] of hydrated HEWL powder it was shown that the water of hydration undergoes anisotropic motion. For purposes of the present discussion we assume that a small fraction fwb (not necessarily the same as the one considered above) of water molecules undergoes anisotropic motion while attached to the HEWL molecule via hydrogen bonds for a time at least as long as the protein tumbling time.…”
Section: Model For Water Molecule Dynamics In Hewl Solutionsmentioning
confidence: 99%